Heteroatom functionalized activated porous biocarbons and their excellent performance for CO2 capture at high pressure. Issue 40 (2nd October 2017) - Singh, Gurwinder; Kim, In Young; Lakhi, Kripal S.; Joseph, Stalin; Srivastava, Prashant; Naidu, Ravi; Vinu, Ajayan
Abstract : Activated biocarbons with a porous structure and nitrogen functionalities are synthesized from the prolific waste biomass, Arundo donax, and an organic material, chitosan, by a simple one step chemical activation with ZnCl2 . Abstract : Activated biocarbons with a porous structure and nitrogen functionalities are synthesized from the prolific waste biomass, Arundo donax, and an organic material, chitosan, by a simple one step chemical activation with ZnCl2 . The nitrogen functional groups in the porous activated biocarbons are significantly increased by the addition of chitosan in the synthesis mixture. The textural properties and N content can easily be tuned by varying the amount of activating agent and the carbonization temperature. The optimized biocarbon sample was obtained at a fairly low carbonization temperature of 500 °C by employing an impregnation mass ratio of ZnCl2 to Arundo donax /chitosan of 3. This optimized material exhibits the best specific surface area of 1863 m 2 g −1, pore volume of 1.0 cm 3 g −1 and nitrogen content of 5.4 wt%. The presence of nitrogen functionalities on the materials provides a negatively charged surface which is critical for the adsorption of CO2 molecules which are acidic in nature. The sample shows remarkable adsorption capacities of 18.2 mmol g −1 at 0 °C/30 bar and 13.1 mmol g −1 at 25 °C/30 bar under the conditions corresponding to pre-combustion CO2 capture from flue gas streams. High CO2 adsorption values of 3.6 mmol g −1 at 0 °C/1 bar and 2.1 mmol g −1 at 25 °C/1 bar are also observed under post-combustion CO2 capture conditions of the material. The N-doped activated biocarbon shows an exceptionally high value of isoelectric heat of adsorption (32.2 kJ mol −1 ), indicating that the surface polarity generated by N dopant plays a crucial role in enhancing interactions between CO2 and porous N-doped activated biocarbons.